Diseño de un sistema de costos en la empresa "Hormigonera Manabí", ubicada en el cantón Quito, provincia de Pichincha. - Espinosa Espinosa, Ana Gabriela (2020)
In the present integrating project, the cost system was analyzed in " Manabí concrete producer " company, which is dedicated to concrete production in different resistances, the company showed several problems in the determination of cost production for not having an appropriate costing and controls system that allows the suitable managing of the cost elements, in addition, the price was established empirically, which was reflected in the inadequate decision making and loss of competitiveness. This research had the objective to design a cost system for the concrete producer that allowed the determination of the real cost in the concrete manufacture, through the situational diagnosis and identification of cost elements. In the methodological field, the quantitative method was considered as a statistical tool that allowed the researchers to get results through interviews and surveys applied to the managers and workers, which were analyzed and interpreted; with the field research, information related to production costs was collected. The impact generated inside the company was positive on the technical, social and economic aspects as it contributed to administrative control and reduction of losses in materials and labor. At the end of the cost system study, the design and application of an electronic sheet to produce orders was established, which had a ninety-five percent in the calculation of costs effectiveness. It contributed to make the decision by the accountant in the financial management, fulfilling the tests made in the cost sheets, production orders, number of orders and costs of orders made; establishing the value invested by the company in the concrete production with the utility of each process